A controller to perform a visually tracking task in laboratory environment - Intan Maisarah, Abd Rahim (Universiti Malaysia Perlis, 2008)
This project is to develop the software for controller to perform a visually guided tracking task in laboratory environment. The image processing include image conversion, applying filter to remove noise, edge detection, and finding the point reference for the robot to move. The Microsoft Visual C++ program is used to do the processing. From the image input, the program will process the image and give the output for the mobile robot. However, my scope of studies is just until the image processing and finding the references point.